2012
DOI: 10.1021/nl303663n
|View full text |Cite
|
Sign up to set email alerts
|

Optical Pumping of a Single Electron Spin Bound to a Fluorine Donor in a ZnSe Nanostructure

Abstract: Here we demonstrate optical pumping of a single electron within a semiconductor nanostructure comprised of a single fluorine donor located within a ZnSe/ZnMgSe quantum well. Experiments were performed to detect optical pumping behavior by observing single photons emitted from the nanostructure when the electron changes spin state. These results demonstrate initialization and read-out of the electron spin qubit and open the door for coherent optical manipulation of a spin by taking advantage of an unconventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The splitting of the D 0 X state is defined solely by the hole spin. Due to confinement and strain in the structure, only the low energy HH states with spin ±3/2 are considered 18 , 19 . The schematic in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The splitting of the D 0 X state is defined solely by the hole spin. Due to confinement and strain in the structure, only the low energy HH states with spin ±3/2 are considered 18 , 19 . The schematic in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, extensive studies have been conducted on systems such as defect centers in diamonds12, quantum dots3, and impurity atoms in semiconductors4. The nuclear spin of rare-earth (RE) ions doped in an inorganic crystal is also a suitable system for quantum-information processing5.…”
mentioning
confidence: 99%
“…This system emerged some years ago as a good prototype for spintronic applications, since experimental studies revealed that the localization of the electron wave function leads to an enhancement of the spin relaxation time. Besides, they present a higher degree of optical orientation of the electron spins than in three-dimensional crystals, and the integration of impurities does not lead to large inhomogeneities [25][26][27][28]. We have adapted the formalism used in Ref.…”
Section: Introductionmentioning
confidence: 99%